Empirical investigation on the effects of disclosure of intended use of IPO proceeds on underpricing in Singapore - Liang, Huimin (2008)
This study mainly investigates underpricing in Singapore context based on 175 entrepreneur IPO firms in Singapore exchange Mainboard and Sesdaq. It include investigation of association of underpricing and the base variables market sentiments, board listing, use of prestigious underwriters, good quality auditors, Year 1999 and percentage of retained ownership (alpha). To examine the effects of voluntary disclosure of risk factors on underpricing.